Investigating Students’ Mathematical Literacy in PISA Tasks Using Newman’s Theory - Wahyudi, Dwi Arisma; Prabawanto, Sufyani (IndoMath: Indonesia Mathematics Education, 2026)
This study investigates the gap between technological ubiquity and stagnant mathematical literacy among Indonesian students. The research objective was to identify and analyze specific cognitive hurdles hindering students’ ability to solve contextual, PISA-adapted problems. Utilizing a qualitative descriptive design, the study involved 34 ninth-grade students in Kabupaten Bandung Barat. Subjects for semi-structured interviews were selected via purposive sampling, targeting those demonstrating representative error patterns across high, moderate, and low proficiency tiers. Data were analyzed using Newman’s Error Analysis (NEA) and validated through methodological triangulation. Results revealed that 52.94% of students possess low mathematical literacy, with the most critical barrier being transformation errors (58.36%), followed by comprehension (27.94%) and reading (14.70%). Qualitative findings indicate that these errors stem from three primary factors: contextual unfamiliarity with non-routine tasks, a detrimental dependency on teacher scaffolding, and conceptual deficits in processing decimal notation. The study concludes that students struggle to bridge the gap between narrative contexts and mathematical formalization. To mitigate these barriers, the research recommends the implementation of incremental scaffolding and explicit instructional strategies focusing on linguistic-to-mathematical translation to foster learner autonomy and higher-order thinking skills in the Indonesian educational framework.